1999
DOI: 10.1038/sj.leu.2401281
|View full text |Cite
|
Sign up to set email alerts
|

Cell biology of CML cells

Abstract: At the cellular level, expansion of haemopoiesis in chronic myeloid leukaemia (CML) must involve some imbalance in cell production along the myeloid maturation pathway. The relevant kinetic parameters are cell loss by apoptosis and differentiation and cell gain by proliferation (self-renewal). In spite of the predominance of the BCR-ABL-positive leukaemic cells, some BCR-ABL-negative, presumably normal, progenitor cells remain for long periods in chronic phase CML. Thus, understanding the kinetics of CML and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
(26 reference statements)
0
28
0
4
Order By: Relevance
“…Delayed apoptosis is a feature of early phase CML, 16 but even more so of advanced disease stages in which upregulation of Table 2b Primer sequences Q-PCR BCR-ABL is a common event. 17.…”
Section: Apoptosis Related Genesmentioning
confidence: 99%
“…Delayed apoptosis is a feature of early phase CML, 16 but even more so of advanced disease stages in which upregulation of Table 2b Primer sequences Q-PCR BCR-ABL is a common event. 17.…”
Section: Apoptosis Related Genesmentioning
confidence: 99%
“…Although the p210 BCR/ABL itself does not significantly affect terminal cell differentiation in chronic phase, differentiation is blocked in blast phase CML. [93][94][95] The role of BCR-ABL itself or other events in this phenomenon is not fully elucidated. Additional mutations, formation of new oncogenes, elevated cytokine levels, inactivation of tumor suppressor genes are hypothetical reasons for this phenomenon.…”
Section: Differentiation Blockmentioning
confidence: 99%
“…This results in the juxtaposition and fusion of parts of the BCR and ABL genes on the Philadelphia (Ph) chromosome and the production of a protein tyrosine kinase (p210 bcr/abl ) that is presumed to be responsible for the biological and clinical features of the disease. 1,2 Interferon (IFN)-␣ has been used to treat CML patients with beneficial results in terms of haematological response and re-emergence of Ph chromosome-negative haemopoiesis. 3,4 Moreover, there is a significant survival advantage compared with alternative forms of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have found that the tyrosine kinase inhibitor, STI571, also preferentially suppresses the replating ability of CML CFU-GM. 12 Since the CFU-GM compartment is the fastest expanding component of the myeloid series in untreated CML, 2,13,14 these findings suggest that at least part of the mode of action of IFN-␣ and STI571 is to selectively reduce the expansion of the leukaemic clone at the myeloid progenitor cell level.…”
Section: Introductionmentioning
confidence: 99%